A Rare Case of Isolated Right Ventricular Non-compaction With the Novel TTN Mutation - Piao-piao Huang; Ya-xin Tang; Xian-sheng Huang (Frontiers in Cardiovascular Medicine, 2022)
Isolated right ventricular non-compaction (RVNC) is rare yet life-threatening if left untreated, especially when accompanied by ventricular tachycardia. We describe a rare case of isolated RVNC, presenting as a prominent and excessive trabeculation of the right ventricle (RV), with an abnormal electrocardiogram. The transthoracic echocardiography, computed tomography, and ventricular angiography results clearly demonstrated an isolated spongy RV, both anatomically and functionally. Genetic testing identified a missense mutation of TTN. Combined, the diagnosis of RVNC was established. The subsequent combination of heart failure therapy, antiarrhythmic, and anticoagulation therapy were effective with a favorable outcome. This case report describes the possible etiology, manifestation, characteristic images, and problematic diagnostic criteria of the isolated RVNC. This case also emphasizes the necessity for comprehensive cardiac screening in familial cardiomyopathy.